2017
DOI: 10.1332/239788217x14937990731730
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of questionnaires used to measure the time spent on family care for frail older people

Abstract: Time spent on family care of frail older people is difficult to substantiate because of its complex nature. The aim of this study is to check the content validity of existing questionnaires measuring the time spent on caring. Comparing the activities mentioned in the questionnaires with those from other data sources (three validated scales measuring the functional limitations in day-to-day activities and a qualitative study) enabled identification of important drawbacks in the questionnaires reviewed. A compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…ICGs filled out the 12-item Zarit-Burden-Interview (ZBI-12) to assess the level of caregiver burden [22]. The cost of living at home, including time spent caring and use of formal care and support services was assessed by an ad-hoc economic questionnaire made for this study [23].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICGs filled out the 12-item Zarit-Burden-Interview (ZBI-12) to assess the level of caregiver burden [22]. The cost of living at home, including time spent caring and use of formal care and support services was assessed by an ad-hoc economic questionnaire made for this study [23].…”
Section: Data Collectionmentioning
confidence: 99%
“…A possible explanation for the large correlation between the two variables could be that many cohabiting ICG filled out that they spent 24 hours per day on caring. Time spent caring is an important factor in determining the role of the ICG, as well as distance for non-cohabiting ICG [23,28].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Sometimes particular tasks are specified. The systematic review of activity lists by Cès et al (2017) found considerable variation in these, and suggested that in many cases, carers' time commitments to different activities were not being effectively measured, as studies take an uncritical view of time as quantifiable clock time.…”
Section: Introductionmentioning
confidence: 99%
“…the annual American Time Use Survey (ATUS); Hamermesh et al, 2005) using prescribed time intervals or allowing a respondent to specify how long a particular task took, and questionnaires asking for example 'how much time do you spend each day on x?' (Cès et al, 2017). Advances in IT and statistics have allowed increasingly complex analyses of data so generated, including identification of patterns and exploration of influences on time use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation